Persistent Ambipolar Heptacenes and Their Redox Species. Issue 26 (5th May 2022) - Zeitter, Nico; Hippchen, Nikolai; Maier, Steffen; Rominger, Frank; Dreuw, Andreas; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract: Sixfold TIPS‐ethynylation combined with fourfold bromination of the armchair edges furnishes a long‐lived, soluble heptacene; π‐extension via Stille coupling accesses a persistent tetrabenzononacene. Both types of acenes were stabilized best by double TIPS‐ethynylation on every other benzene ring. Tetrabromoheptacene is an ambipolar transistor material (up to 0.036 cm 2 V −1 s −1 n‐channel), which was corroborated by generation of its monoanion and monocation. Abstract : Soluble heptacenes are stabilized via TIPS‐ethynylation and halogenation. TIPS‐ethynylation on every second ring is critical for longevity. The most stable derivative is characterized in thin‐film transistors and post‐functionalized via Stille coupling to a nonarene.